How often is occult atrial fibrillation in cryptogenic stroke causal vs. incidental? A meta-analysis - Chaisinanunkul, Napasri; Khurshid, Shaan; Buck, Brian H.; Rabinstein, Alejandro A.; Anderson, Christopher D.; Hill, Michael D.; Fugate, Jennifer E.; Saver, Jeffrey L. (Frontiers in Neurology, 2023)
Introduction Long-term cardiac monitoring studies have unveiled low-burden, occult atrial fibrillation (AF) in some patients with otherwise cryptogenic stroke (CS), but occult AF is also found in some individuals without a stroke history and in patients with stroke of a known cause (KS). Clinical management would be aided by estimates of how often occult AF in a patient with CS is causal vs. incidental. Methods Through a systematic search, we identified all case–control and cohort studies applying identical long-term monitoring techniques to both patients with CS and KS. We performed a random-effects meta-analysis across these studies to determine the best estimate of the differential frequency of occult AF in CS and KS among all patients and across age subgroups. We then applied Bayes' theorem to determine the probability that occult AF is causal or incidental. Results The systematic search identified three case–control and cohort studies enrolling 560 patients (315 CS, 245 KS). Methods of long-term monitoring were implantable loop recorder in 31.0%, extended external monitoring in 67.9%, and both in 1.2%. Crude cumulative rates of AF detection were CS 47/315 (14.9%) vs. KS 23/246 (9.3%). In the formal meta-analysis, the summary odds ratio for occult AF in CS vs. KS in all patients was 1.80 (95% CI, 1.05–3.07), p = 0.03. With the application of Bayes' theorem, the corresponding probabilities indicated that, when present, occult AF in patients with CS is causal in 41.2% (95% CI, 15.5–77.7%) of patients. Analyses stratified by age suggested that detected occult AF in patients with CS was causal in 62.3% (95 CI, 0–87.1%) of patients under the age of 65 years and 28.5% (95 CI, 0–63.7%) of patients aged 65 years and older but estimates had limited precision. Conclusion Current evidence is preliminary, but it indicates that in cryptogenic stroke when occult AF is found, it is causal in about 41.2% of patients. These findings suggest that anticoagulation therapy may be beneficial to prevent recurrent stroke in a substantial proportion of patients with CS found to have occult AF.